Dupilumab in Adults with Moderate-to-Severe Atopic Dermatitis and Prior Use of Systemic Non-Steroidal Immunosuppressants: Analysis of Four Phase 3 Trials - Griffiths, Christopher (Dermatol Ther (Heidelb), 2021)
INTRODUCTION: Dupilumab is approved as first-line systemic treatment for adults/adolescents with moderate-to-severe atopic dermatitis (AD) in Europe and elsewhere owing to its favourable benefit–risk profile. However, systemic non-steroidal immunosuppressants (NSISS) are often used as first-line therapy in clinical practice. Impact of prior therapy with NSISS on dupilumab’s treatment effect vs. control has not been described previously. This study assessed dupilumab’s efficacy vs. control in patients with moderate-to-severe AD, comparing treatment effect in patients with/without prior systemic NSISS therapy, in four phase 3 trials. METHODS: This post hoc analysis included 1553 patients randomized to placebo or dupilumab (300 mg q2w) as monotherapy for 16 weeks, or with concomitant topical corticosteroids (TCS) for 16/52 weeks, from four randomized, double-blind, placebo-controlled, phase 3 trials. Patients were stratified by prior use of systemic NSISS and dupilumab-treated patients were analysed against control groups (treated with placebo or placebo + TCS). RESULTS: Dupilumab-treated patients, regardless of prior treatment with NSISS, achieved a significantly higher percentage reduction from baseline in Eczema Area and Severity Index (EASI), SCORing Atopic Dermatitis (SCORAD), Dermatology life Quality Index (DLQI), and Patient-Oriented Eczema Measure (POEM) vs. control; significantly more achieved EASI score ≤ 7, Peak Pruritus Numerical Rating Scale ≤ 4, POEM ≤ 7, and DLQI ≤ 5 by week 4. These rapid, significant improvements were seen with or without concomitant TCS and sustained through end-of-treatment. CONCLUSIONS: Dupilumab treatment (monotherapy or + TCS) provides rapid, significant, sustained improvements in signs, symptoms, and quality of life in patients with moderate-to-severe AD compared with control, regardless of prior systemic NSISS use. CLINICAL TRIAL REGISTRATION: LIBERTY AD SOLO 1: ClinicalTrials.gov identifier NCT02277743, EudraCT 2014-001198-15. LIBERTY AD SOLO 2: ClinicalTrials.gov identifier NCT02277769, EudraCT 2014-002619-40. LIBERTY AD CHRONOS: ClinicalTrials.gov identifier NCT02260986, EudraCT 2013-003254-24. LIBERTY AD CAFÉ: ClinicalTrials.gov identifier NCT02755649, EudraCT 2015-002653-35. GRAPHIC ABSTRACT: [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13555-021-00558-0.